The Gingerbread Bear - Dennis, Robert, 1944-2011.; Lyon, Tammie (New York, N.Y. : Cartwheel Books, 2012)
In this variation of the Gingerbread man, the Gingerbread Bear runs through Woodlands National Park, until he encounters the clever ranger.
Keywords: Gingerbread boy -- Adaptations; Gingerbread men -- Juvenile fiction; Cookies -- Fiction